Pendampingan Remaja Masjid Rutinan Tadarus Setiap Malam Jumat Untuk Meningkatkan Minat Mengaji Masyarakat di Masjid Al Amanah Ngingas Waru Sidoarjo - Amirul Shidiq; Riyan Ashari; Afif Rofi Ubaidillah; Moch Edo Septianto; Muhammad Yusron Maulana El-Yunusi (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The activity of mentoring mosque youth in the routine of tadarus every Friday night at the Al Amanah Mosque, Ngingas, Waru, Sidoarjo aims to increase interest in studying the Koran in the community, especially among teenagers. Through the Asset Based Community Development (ABCD) approach, this service utilizes local potential such as the spirit of mutual cooperation, the presence of active mosque youth, and support from religious figures. The results of the activity show an increase in community participation in tadarus, an increase in the ability to read the Koran, and the formation of religious character and social solidarity between residents. This activity not only makes the mosque a place of worship, but also a center for inclusive and sustainable religious learning. Active participation of teenagers in tadarus activities is also a means of developing leadership and forming Islamic character. This activity is expected to be a model of religious-based community empowerment that can be replicated in other environments with ongoing support from various parties.